Metode Pinhole Model untuk Menentukan Jarak Perpindahan Kendaraan dalam Video - Rizki Yusliana Bakti (Universitas Muhammadiyah Makassar, 2019)
Intelligent Transportation System is a solution to overcome the problem of transportation. The purpose of this study was to design a system to calculate the distance of vehicle movement in the video. One example of application of intelligent transport system is to calculate the speed of a vehicle that can be used in traffic engineering. Parameters used to obtain the speed of the vehicle is the distance parameter. The distance of vehicle movement in the video can be obtained by using a pinhole camera calibration model. An appropriate calibration of camera can provide the intended parameter. There are several stages to perform calculation of the distance of object movement. The first stage was a detection of vehicle within the frame. The detection was required to obtain the center point of vehicle object. The next stage was to detect an object within the frame. This was performed to understand the movement of object from one frame to another frame. The data used for the study were video data with mov format. The result of research showed that the method of pinhole model was applicable to calculate the distance of object movement in video. The application of this method can help in calculating the object distance without manual calculation.